A study on public understanding towards belt and road initiative (BRI) projects in Malaysia - Lee, Si Ying (2019)
There are two problem statements in this study. Firstly, the Belt and Road Initiative (BRI) projects typically involve large corporations and business people which neglect the farmers, grassroots, students and small and medium enterprises. Secondly, BRI presents unclear and hysteria image to the public as no one really know what the initiative really is. Moreover, this study aims to examine the public understanding towards BRI projects in Malaysia and assess the public perception towards the involvement of Malaysia in BRI. As for methodology, quantitative research is used in this study. Internet survey on Google Forms will be distributed to public in Malaysia. The survey reached to a sample of 200 respondents. The data collected will be further analysed. The results show that the respondents in Malaysia have low level of understanding towards BRI projects in Malaysia. Despite of that, majority of the respondents have positive perception towards the BRI projects in Malaysia. Several parties are the key drivers to obtain better understanding and perception of the public towards BRI projects in Malaysia. Firstly, the government needs to have a clear framework and regulations on BRI projects. The organizations should promote more on the BRI projects. Moreover, the media also plays an important role in increasing public understanding and perception towards BRI projects in Malaysia. The media needs to have efficient flow of information. Lastly, education institutions and universities should take part in engaging students and academics. With more exposure of BRI projects, universities can now collaborate with other international universities.